2013
DOI: 10.1159/000350570
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in a Stroke Patient on Dabigatran Anticoagulation: Case Report and Synopsis of Published Cases

Abstract: We present the case of an aphasic 77-year-old stroke patient with left distal M1 occlusion who received rt-PA for thrombolysis while on oral anticoagulant treatment with dabigatran (150 mg b.i.d.). Coagulation parameters were normal (thrombin time 20 s, aPTT 20 s, INR 1.08) and the patient improved from an NIHSS of 15 to 5 within 24 h with sonographic evidence of M1 recanalization. She did not develop intracranial bleeding complications but showed unusually large diffuse skin ecchymoses. In our report, we give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…8,9 The knowledge about IVT in NOAC patients is limited and based on case reports. [14][15][16][17][18]20,21,24 Data from animal models showed no excessive risk of ICH after IVT in rodents with a prior treatment with rivaroxaban, 43,44 dabigatran, 45,46 and apixaban 44 in comparison with VKA. Currently, the use of IVT for acute ischemic stroke in patients with a recent (<48 hours) intake of a NOAC is regarded off-label.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The knowledge about IVT in NOAC patients is limited and based on case reports. [14][15][16][17][18]20,21,24 Data from animal models showed no excessive risk of ICH after IVT in rodents with a prior treatment with rivaroxaban, 43,44 dabigatran, 45,46 and apixaban 44 in comparison with VKA. Currently, the use of IVT for acute ischemic stroke in patients with a recent (<48 hours) intake of a NOAC is regarded off-label.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Furthermore, a few case reports on the use of IVT in patients taking dabigatran, [14][15][16][17][18] rivaroxaban, [19][20][21][22] or apixaban, 23 or IAT while taking dabigatran 24 reported favorable clinical outcomes. Conversely, 1 patient with ischemic stroke under dabigatran treatment had a fatal intracranial hemorrhage (ICH) associated with IVT.…”
Section: Clinical Perspective On P 1269mentioning
confidence: 99%
“…Kate argues that even subtherapeutic plasma concentrations of dabigatran and other antithrombotic agents exert a protective effect by reducing clot burden and/or increasing the likelihood of spontaneous recanalization . Pfeilschifter et al reported that all cases of stroke under dabigatran which received t‐PA so far did not show relevant alterations of the aPTT . While noncompliance may be an issue for DOACs, our patient plausibly denied irregular intake.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast to patients taking VKAs with an INR of ≤1.7 that can be considered for treatment with intravenous recombinant tissue plasminogen activator (rtPA), ischemic stroke patients taking NOACs are typically excluded from treatment with intravenous rtPA. Although isolated case reports exist describing variable outcomes in acute ischemic stroke patients treated with thrombolysis while taking dabigatran [12], there is lack of consensus on how vascular neurologists would treat otherwise rtPA-eligible patients [13]. Large, well-designed studies will be necessary to determine if rapidly measured anticoagulant effect of NOACs can predict symptomatic intracranial hemorrhage or functional outcomes following thrombolysis.…”
Section: Stroke Prevention In Atrial Fibrillationmentioning
confidence: 99%